2015
DOI: 10.1111/jnc.13198
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective arylpiperazine dopaminergic/serotonergic ligands suppress experimental autoimmune encephalomyelitis in rats

Abstract: Arylpiperazine-based dopaminergic/serotonergic ligands exert neuroprotective activity. We examined the effect of arylpiperazine D 2 /5-HT 1A ligands, N-{4-[2-(4-phenyl-piperazin-1-yl)-ethyl}-phenyl]-picolinamide (6a) and N-{3-[2-(4-phenyl-piperazin-1-yl)-ethyl]-phenyl}-picolinamide (6b), in experimental autoimmune encephalomyelitis (EAE), a model of neuroinflammation. Both compounds (10 mg/kg i.p.) reduced EAE clinical signs in spinal cord homogenate-immunized Dark Agouti rats. Compound 6b was more efficient i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…We have combined data demonstrating that the enteral flora influences the peripheral and central SS 5 7 , 10 , 12 , 13 with clinical studies which provide evidence for lowered SS functionality in MS patients. 15 20 In our opinion, these data strongly suggest a role of the gut microbiome in the alterations of the SS in MS. To further strengthen our hypothesis, we looked into studies on the effects of 5-HT on macrophages, DCs, and T cells 21 25 – key players in MS. Although there is a need for greater understanding of the effects of 5-HT on cellular immunity and neuroinflammation specifically, the discussed studies provide a plausible theoretical framework linking decreased levels of 5-HT to inflammation in MS.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…We have combined data demonstrating that the enteral flora influences the peripheral and central SS 5 7 , 10 , 12 , 13 with clinical studies which provide evidence for lowered SS functionality in MS patients. 15 20 In our opinion, these data strongly suggest a role of the gut microbiome in the alterations of the SS in MS. To further strengthen our hypothesis, we looked into studies on the effects of 5-HT on macrophages, DCs, and T cells 21 25 – key players in MS. Although there is a need for greater understanding of the effects of 5-HT on cellular immunity and neuroinflammation specifically, the discussed studies provide a plausible theoretical framework linking decreased levels of 5-HT to inflammation in MS.…”
Section: Discussionsupporting
confidence: 51%
“… 16 Similarly, treatment with arylpiperazine ligands, which bind to 5-HTR1A and dopamine receptor 2, demonstrates that combined serotonergic and dopaminergic stimulation has a neuroprotective effect and reduces CNS immune infiltration in EAE mice. 17 Clinical investigations have also explored the effects of fluoxetine – a selective 5-HT re-uptake inhibitor, which increases the concentration of 5-HT in the CNS of MS patients. 18 , 19 Fluoxetine – a candidate for drug repurposing 18 is now clinically tested in patients with secondary-progressive MS as a neuroprotective compound.…”
Section: Altered Ss In Msmentioning
confidence: 99%
“…Some of the arylpiperazines that are in use in clinics have neuroprotective activity . In our previous publications, we already described neuroprotective properties of N ‐{[2‐(4‐phenyl‐piperazin‐1‐yl)‐ethyl]‐phenyl}‐arylamides …”
Section: Resultsmentioning
confidence: 99%
“…In our previous publications, we demonstrated that N ‐{[2‐(4‐phenyl‐piperazin‐1‐yl)‐ethyl]‐phenyl}‐arylamides of the structural formula shown in Scheme provides neuroprotection in vitro and in vivo through a stabilizing mitochondria function but not through their dopaminergic and serotonergic properties . In cell‐based model of nitric oxide‐mediated neurotoxicity, their protective effect was associated with the inhibition of proapoptotic (JNK, ERK, and AMPK) and activation of antiapoptotic (Akt) signaling pathways .…”
Section: Introductionmentioning
confidence: 96%
“…In 2015, a research team studied for the first time the effects of aryl piperazine D2/5-HT 1A ligands in rats with EAE. It demonstrated not only symptomatic improvement and a delay in the disease's progression, but also a decreased cell death rate with the protection of oligodendrocytes and neurons from T lymphocytes [29]. Even though the above studies have shown amelioration of EAE in animals and, in some cases, protection against the immune attack, it is essential to consider that both agents act on more than just the serotonergic system.…”
Section: Serotonergic System-modulating Drugsmentioning
confidence: 99%